Effectiveness of Behavioral Activation Therapy on Sexual Dysfunction and Relationship Satisfaction of Postmenopausal Women with Sexual Desire-Arousal Disorder: Effectiveness of behavioral activation therapy on sexual dysfunction and relationship satisfaction of postmenopausal women with sexual desire/arousal disorder - Heidary Shadehi, Somayeh; Sajjadian , Ilnaz; Manshaee, Gholam Reza (International Journal of Applied Behavioral Sciences, 2023)
Background and Aim:Menopause is a critical phase in women’s lives that can lead to various long-term issues, including a decrease in sexual desire and arousal, which may negatively affect their quality of life. Sexual dysfunction is closely linked to women’s cognitive beliefs. This study aims to evaluate the effectiveness of behavioral activation therapy on dysfunctional sexual beliefs and relationship satisfaction in menopausal women experiencing sexual. Materials and Methods:This quasi-experimental study employed a pre-test-post-test design and follow-up with a control group. The statistical population included all menopausal women with sexual dysfunction over the age of 50 who referred to specialized treatment centers for sexual disorders in Isfahan in 2023. Thirty menopausal women with sexual dysfunction were selected through purposive sampling and clinical interviews, with a sexual function score of less than 28 based on the Rosen Female Sexual Function Index. They were randomly assigned to either the intervention group (n=15) who received eight 90-minute sessions of behavioral activation therapy or the control group (n=15) who were placed on the waiting list without receiving any intervention. The Dysfunctional Sexual Belief Questionnaire (DSBQ), the Relationship Satisfaction Scale and Female Sexual Function Index (FSFI) were used as data collection tools. The data were analyzed using repeated measures ANOVA in SPSS version 23. Results:The results showed a significant difference between the mean scores of dysfunctional sexual beliefs and relationship satisfaction in the pre-test with post-test and follow-up in the intervention group (p<0.05). Therefore, it can be concluded that dysfunctional sexual beliefs and relationship satisfaction improved in the post-test and follow-up compared to the pre-test, and the scores remained stable in the follow-up compared to the post-test (p<0.05). Conclusion:Based on the findings, behavioral activation therapy can improve sexual dysfunctional beliefs and relationship satisfaction in postmenopausal women with sexual desire/arousal disorders by increasing the person’s contact with environmental reinforcing connections and improving mood and thinking. to empower sexual challenges and pave the way for further research in the field of interventions related to menopausal women with sexual desire/arousal disorders. Therefore, it is suggested to use behavioral activation therapy in health and treatment centers and counseling centers to improve the sexual problems of postmenopausal women.